Tingkat Efektifitas Regulasi dan Sistem Keamanan Terhadap Penurunan Keresahan Pengguna E-wallet - Roland Fran Vernando; Diana Frederica; Christy Theodora; Victor Saputera Harefa; Sherly Sherly; Cynthia Theodora (LPPM UBP, 2022)
With the rapid development of technology, the transfer of cash into e-wallet has increased significantly. E-wallet is the choice in the current era because it is considered more practical and effective. As Fintech develops, the security system provided must improve so that it can reduce user anxiety in using e-wallet as a means of payment transactions. In this paper, we discuss the regulation and security system of e-wallet in Indonesia against the anxiety experienced by users. The purpose of this study is to analyze whether the effectiveness of regulation can reduce the anxiety of e-wallet users and analyze whether the security system can reduce the anxiety of e-wallet users. This research method uses descriptive analysis method with primary data. The subjects of this research are university students, students and workers. Data were collected through questionnaires distributed to 135 respondents. The results of this study indicate that improving the security system and regulation of e-wallet is very important. Users provide suggestions for the addition of new features that can support a more definite security system such as the addition of Face Scanning. The conclusion of this study is that with strong regulations, the security system in the e-wallet will be more reliable so that it can reduce the level of user anxiety.